2017
DOI: 10.1007/s00277-017-3060-4
|View full text |Cite
|
Sign up to set email alerts
|

Biosimilar G-CSF versus filgrastim and lenograstim in healthy unrelated volunteer hematopoietic stem cell donors

Abstract: The World Marrow Donor Organization recommends original granulocyte-colony stimulating factor (G-CSF) for the mobilization of stem cells in healthy unrelated hematopoietic stem cell donors. We report the comparison of a biosimilar G-CSF (Zarzio) with two original G-CSFs (filgrastim and lenograstim) in mobilization in unrelated donors. We included data of 313 consecutive donors who were mobilized during the period from October 2014 to March 2016 at the Medical University of Warsaw. The primary endpoints of this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 9 publications
1
12
0
2
Order By: Relevance
“…On the other hand, the use of biosimilar G‐CSFs for stem cell mobilization in healthy donors was initially met with less enthusiasm although evidence on their safety and efficacy is accumulating . Results from a large retrospective study reported similar findings to ours using the biosimilar G‐CSF Zarzio (Sandoz, Germany) in n = 85 donors compared with patients who received Neupogen and lenograstim, without observing a difference in the number of CD34+ cells collected in the first apheresis session and a 93% first‐apheresis success rate, similar to patients who received the originator and superior to lenograstim . The largest prospective study reported to date in healthy donor mobilization was performed using the Sandoz brand and reported a 91% success rate in one apheresis and demonstrated its safety .…”
Section: Discussionsupporting
confidence: 64%
“…On the other hand, the use of biosimilar G‐CSFs for stem cell mobilization in healthy donors was initially met with less enthusiasm although evidence on their safety and efficacy is accumulating . Results from a large retrospective study reported similar findings to ours using the biosimilar G‐CSF Zarzio (Sandoz, Germany) in n = 85 donors compared with patients who received Neupogen and lenograstim, without observing a difference in the number of CD34+ cells collected in the first apheresis session and a 93% first‐apheresis success rate, similar to patients who received the originator and superior to lenograstim . The largest prospective study reported to date in healthy donor mobilization was performed using the Sandoz brand and reported a 91% success rate in one apheresis and demonstrated its safety .…”
Section: Discussionsupporting
confidence: 64%
“…Prospective study of biosimilar filgrastim ( n = 85) vs. lenograstim ( n = 121) and ref filgrastim ( n = 107) for allogeneic SCM [48]…”
Section: Biosimilar Filgrastim Phase III Clinical Datamentioning
confidence: 99%
“…Filgrastim and lenograstim are growth factors of choice for mobilizing PBSCs in HDs [9]. Recent evidence supports the safety and efficacy of G-CSF biosimilars for PBSC mobilization in the AlloSCT setting [10,11]. The recommended G-CSF dose is 10 mg/kg/body weight (BW) daily [12], by subcutaneous injection, in daily or twice-daily dosing [13].…”
Section: Introductionmentioning
confidence: 99%